Modelling the subjective experience of fun at work. Issue 3 (4th December 2018) - Clancy, Maeve; Linehan, Carol
Abstract : Purpose: The purpose of this paper is to explain some divergent findings on experiences of fun at work. It explains conflicting findings by moving from a focus on classifying the activity (as, e.g. task/managed/organic) to foregrounding the dynamics of the experience, adding to the growing conceptualisation of fun at work as a multi-dimensional construct. Design/methodology/approach: This research draws on empirical data obtained through case study and interviews with 13 participants from two organisations. These interviews were subjected to intense thematic analysis. Findings: It was found that an individual's underlying beliefs about the organisation; the perceived drivers of the fun practice; and the level of control exerted over a fun practice significantly shape the experience. The paper draws on the concept of the psychological contract to frame the relationship between these three key interacting elements. Practical implications: This paper provides a greater understanding of the dynamics of fun experiences, enabling management to better recognise and contextualise the impact of fun practices. Originality/value: Given conflicting findings on both the experience and outcomes of fun at work, this study elucidates the dynamics underpinning the experience of fun at work. It is novel to consider experiences of fun through the lens of psychological contracts, which offers fresh insight into the understanding of individual experiences of fun.